a) \(\dfrac{5}{24}+x=\dfrac{7}{12}\)
<=> \(x=\dfrac{7}{12}-\dfrac{5}{24}=\dfrac{14}{24}-\dfrac{5}{24}=\dfrac{9}{24}=\dfrac{3}{8}\)
b) \(x-\dfrac{3}{4}=\dfrac{1}{2}\)
<=> \(x=\dfrac{1}{2}+\dfrac{3}{4}=\dfrac{2}{4}+\dfrac{3}{4}=\dfrac{5}{4}\)
c) bn ghi rõ đề chút
ok bạn
(2\7.x+3\7) :2 1\5-3\7=1
hai phần bảy nhân x cộng ba phần bảy chia hai một phần năm trừ 3 phần bảy bằng một
Giải:
a) \(\dfrac{5}{24}+x=\dfrac{7}{12}\)
\(x=\dfrac{7}{12}-\dfrac{5}{24}\)
\(x=\dfrac{3}{8}\)
b) \(x-\dfrac{3}{4}=\dfrac{1}{2}\)
\(x=\dfrac{1}{2}+\dfrac{3}{4}\)
\(x=\dfrac{5}{4}\)
c) \(\left(\dfrac{2}{7}.x+\dfrac{3}{7}\right):2\dfrac{1}{5}-\dfrac{3}{7}=1\)
\(\left(\dfrac{2}{7}.x+\dfrac{3}{7}\right):\dfrac{11}{5}=1+\dfrac{3}{7}\)
\(\left(\dfrac{2}{7}.x+\dfrac{3}{7}\right):\dfrac{11}{5}=\dfrac{10}{7}\)
\(\dfrac{2}{7}.x+\dfrac{3}{7}=\dfrac{10}{7}.\dfrac{11}{5}\)
\(\dfrac{2}{7}.x+\dfrac{3}{7}=\dfrac{22}{7}\)
\(\dfrac{2}{7}.x=\dfrac{22}{7}-\dfrac{3}{7}\)
\(\dfrac{2}{7}.x=\dfrac{19}{7}\)
\(x=\dfrac{19}{7}:\dfrac{2}{7}\)
\(x=\dfrac{19}{2}\)